2010
DOI: 10.5614/itbj.eng.sci.2010.42.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Control with Approximated Policy Search Approach

Abstract: Most of existing adaptive control schemes are designed to minimize error between plant state and goal state despite the fact that executing actions that are predicted to result in smaller errors only can mislead to non-goal states. We develop an adaptive control scheme that involves manipulating a controller of a general type to improve its performance as measured by an evaluation function. The developed method is closely related to a theory of Reinforcement Learning (RL) but imposes a practical assumption mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…AEÇo = K È É sin 3 0O P . For comparison, the application of AFC to both control problems were simulated using the following three cases: Note that cases 1 and 2 are the same as considered in [18], in which Eq. (21) was originally proposed, the update rule with failure detector.…”
Section: Simulations Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AEÇo = K È É sin 3 0O P . For comparison, the application of AFC to both control problems were simulated using the following three cases: Note that cases 1 and 2 are the same as considered in [18], in which Eq. (21) was originally proposed, the update rule with failure detector.…”
Section: Simulations Resultsmentioning
confidence: 99%
“…They are not applicable to plants that cannot be represented by the assumed model structure. Previous research on the same issue as addressed in this paper is reported in [15][16][17][18]. Although the proposed systems work, their performance is poor.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation